One for All : The Logic of Group Conflict - Hardin, Russell (Book collections on Project MUSE., 2001)
In a book that challenges the most widely held ideas of why individuals engage in collective conflict, Russell Hardin offers a timely, crucial explanation of group action in its most destructive forms. Contrary to those observers who attribute group violence to irrationality, primordial instinct, or complex psychology, Hardin uncovers a systematic exploitation of self-interest in the underpinnings of group identification and collective violence. Using examples from Mafia vendettas to ethnic violence in places such as Bosnia and Rwanda, he describes the social and economic circumstances that se.